Calibration method of DR equipment in China–Russia Eastern Gas Pipeline - Quanli LIU; Hui MIAO; Xinyu LYU; Guangyan ZHOU (You-qi chuyun, 2020)
In order to effectively control the welding quality of pipeline girth welds and meet the requirements of intelligent pipeline construction, X-ray Digital Radiography(DR) equipment was used to detect the welding quality of girth welds in China–Russia Eastern Gas Pipeline. The pipeline DR equipment is mainly composed of crawler with X-ray device, detector, computer, inspection software and detection tools, etc., and its reliability is directly related to the inspection quality of pipeline girth welds. At present, the technical indexes are only proposed for each component of DR equipment at home and abroad, and still no calibration method and calibration standard are available for the complete equipment system. Therefore, procedures for calibration of DR equipment in China–Russia Eastern Gas Pipeline have been developed. In addition to the bad pixel, basic spatial resolution, minimum allowable gray scale amplitude and contrast sensitivity of the detector specified in related standards, the DR equipment imaging uniformity, defect detection rate and reliability test have been added as calibration items to provide technical guarantee for the high-quality construction of the China–Russia Eastern Gas Pipeline.